Revealing Charge Transport and Device Operations of Organic Ambipolar Transistors and Inverters by Four‐Probe Measurement. (25th January 2021) - Liu, Chenning; Dai, Fuhua; Liu, Baiquan; Wei, Huan; Chen, Pingan; Hu, Yuanyuan; Wu, Jin; Liu, Chuan
Abstract: Detecting and understanding ambipolar charge accumulation and transport are essential for constructing ambipolar organic field‐effect transistors (OFETs). However, it is difficult to determine carrier motion using general electrical tests. Here, the generalized gated four‐probe (G‐GFP) technique is extended to ambipolar transistors made of diketopyrrolopyrrole‐thieno[3, 2‐b]thiophene copolymer (DPPT‐TT), and the motion of the internal carrier during operation is investigated. The evolution of the local potential is monitored in the channel to establish a clear and quantitative picture of accumulation and transport for two types of carriers during device operation. Both simulation and experimental results verify that G‐GFP is a suitable and accessible approach for extracting the device mobility of ambipolar transistors. An ambipolar device with a G‐GFP structure can function as a single‐OFET inverter, demonstrating that G‐GFP can serve as an effective tool for ambipolar transistor analysis, while simultaneously facilitating the implementation of logic functions. Abstract : The generalized gated four‐probe (G‐GFP) technique is extended to ambipolar transistors made of diketopyrrolopyrrole‐thieno[3, 2‐b]thiophene copolymer (DPPT‐TT) for detecting and understanding ambipolar charge accumulation and transport. Both simulation and experiment are complete. Additionally, this ambipolar device with a G‐GFP structure can function as a single‐organic field‐effect transistor inverter.